Pulmonary effects of contact exposure to paraquat: a clinical and experimental study. Issue 2 (April 1979) - Levin, P J; Klaff, L J; Rose, A G; Ferguson, A D
Abstract : The clinical and pathological features of a patient who died from the effects of percutaneous absorption of paraquat are described. The toxin was absorbed during the spraying of vineyards. Nine of his co-workers, less heavily exposed, were investigated. The transfer factor for carbon monoxide was reduced in six. Lung biopsy of two showed medial hypertrophy of the pulmonary arteries with evidence of fresh and organised thrombi. In one there was also interstitial fibrosis. We designed an experimental animal model to investigate these findings. Low concentrations of paraquat were applied to the skin of rats over a nine-week period. The lungs were examined postmortem, and the medial thickness of the muscular pulmonary arteries was expressed as a percentage of their external diameters. In randomly encountered (large and small) pulmonary arteries the mean percentage medial thickness (MT%) was 11·99±0·41% (SEM) in controls and 25·28±0·94% in test rats (p <0·001). In the large muscular pulmonary arteries the MT% in the control rats was 13·6±0·49% and in the test rats 25·9±1·44% (p <0·001). In the small pulmonary arteries the values were: controls 9·0±0·73% and tests 14·2±1·35% (p <0·05). One test rat which died spontaneously showed pulmonary infarction from thrombosis. We concluded that paraquat absorbed through the skin in low dosage over a prolonged period can produce pulmonary arterial lesions in man and rat. This contrasts with the familiar pathological findings of acute high dose ingestion. These findings have important bearings on the use of this herbicide in agriculture.